2019
DOI: 10.1007/s00787-018-01270-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial risk factors for suicidality in children and adolescents

Abstract: Suicidality in childhood and adolescence is of increasing concern. The aim of this paper was to review the published literature identifying key psychosocial risk factors for suicidality in the paediatric population. A systematic two-step search was carried out following the PRISMA statement guidelines, using the terms 'suicidality, suicide, and self-harm' combined with terms 'infant, child, adolescent' according to the US National Library of Medicine and the National Institutes of Health classification of ages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
127
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(168 citation statements)
references
References 53 publications
19
127
0
5
Order By: Relevance
“…In agreement with previous investigations [8,10,20,25], the ndings of this research show an association between current tobacco use, drug use, parental tobacco use and fast food intake with single and/or multiple suicide attempts. Several mechanisms have been proposed [10] for the link between fast food consumption and suicide attempt, for example, "fast food consumption may increase risk for suicide attempts by increasing vulnerability to traumatic stress via alterations in brain structure and function, with stress being a well-known predictor of suicide attempts in adolescents."…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous investigations [8,10,20,25], the ndings of this research show an association between current tobacco use, drug use, parental tobacco use and fast food intake with single and/or multiple suicide attempts. Several mechanisms have been proposed [10] for the link between fast food consumption and suicide attempt, for example, "fast food consumption may increase risk for suicide attempts by increasing vulnerability to traumatic stress via alterations in brain structure and function, with stress being a well-known predictor of suicide attempts in adolescents."…”
Section: Discussionsupporting
confidence: 93%
“…Only among girls, this study found an association between social-environmental factors (parental tobacco use and parents never/rarely check home work) and multiple suicide attempts, which concurs with some previous research [20,25]. In agreement with former research [15][16][17], this study showed a strong association between multiple adverse experiences and single and multiple suicide attempts, and appeared to be stronger in multiple suicide attempts.…”
Section: Discussionsupporting
confidence: 92%
“…A similar study from Asia in 2015 found the rate of smoking and alcohol consumption to be 22.3% and 27.9% ( 4 ), which were 32.3% and 18.7% in Turkey, respectively ( 5 ). The rate of suicide attempts was higher in adolescents than in other age groups ( 6 ). The higher rates may be due to psychological problems in adolescents such as anxiety and depression, stressful life (problems with peers or family, chronic illness, etc.)…”
Section: Introductionmentioning
confidence: 73%
“…Risk faktörlerinin bilinmesi, intihar girişimi olmadan öncesinde ve tekrarlayan intihar girişimlerinin önlenebilmesinde gerekli koruyucu önlemlerin alınması ve müdahale programlarının geliştirilmesi açısından çok önemlidir. Ergenlik döneminde intihar davranışı için risk faktörlerini araştıran çalışmalarda, başta major depresyon olmak üzere psikiyatrik hastalık varlığı, önceki intihar girişimi, sosyal yetersizlik, stresli yaşam olayları (aile çatışması, akademik stresör, travma, zorbalığa maruz kalma gibi), nörotisisizm ve dürtüsellik gibi mizaç özellikleri risk faktörleri olarak bildirilmiştir (3,4). İntihar davranışını artıran risk faktörlerinden biri de bağlanma sorunlarıdır.…”
Section: Introductionunclassified